Chemical and sensory quality of milk fermented by starter combination of Lactobacillus plantarum Dad 1, Lactococus lactis, and Yeast - Marya, Dina Tri (2017)
Lactobacillus plantarum dad13 is a typical of bacteria from "Dadih"(traditional fermented milk from West Sumatra, Indonesia). The purpose of this study was to evaluate the effect of starter combination of Lactobacillus plantarum dad13, Lactococcus lactis and yeast (Saccharomyces cerevisiae and Kluyveromyces marxianus) on the chemical and sensory quality of fermented milk. The nie cobinations of starter to produce fermented milk were: 1) L. plantarum Dad13, 2) L. plantarum dad13 + L. lactis, 3) L. plantarum Dad13 + S. cerevisiae, 4) L. plantarum dad13 + K. marxianus, 5) L. plantarum Dad13 + L. lactis + S. cerevisiae, 6) L. Plantarum Dad13 + L. lactis+ K. Marxianus, 7) L. lactis, 8) L. lactis + S. cerevisiae, 9) L. lactis + K. marxianus. The evaluated chemical quality of fermented milk included total solid, fat and protein, whereas the sensory quality included taste, aroma, texture and hedonic test. The result showed that combination of starter had no effect on total solid, fat and protein of fermented milk. However, the combination of starter could affect on taste, aroma, texture and hedonic test of fermented milk (p<0.05). Fermented milk from the single starter of L. plantarum Dad13 had the lowest score (P<0.05) for taste, aroma, texture and hedonic test, while other product from the combination of L. plantarum Dad13 + L. lactis + K. marxianus had highest score in taste (P<0.05).